The potential for circular dichroism as an additional facile and sensitive method of monitoring low-molecular-weight heparins and heparinoids - Rudd, Timothy R; Skidmore, Mark A; Guimond, Scott E; Holman, Joseph; Turnbull, Jeremy E; Lauder, Robert M; Fernig, David G; Yates, Edwin A (Thrombosis and haemostasis, 2009)
The ultraviolet circular dichroism (CD) spectra of commercial low-molecular-weight heparins, heparinoids and other anticoagulant preparations have been recorded between 180 and 260 nm. Principal component analysis of the spectra allowed their differentiation into a number of groups related to the means of their production reflecting the structural changes introduced by each process. The findings suggest that CD provides a complementary technique for the rapid analysis of heparin preparations.